Helen said:
Can someone look this over and let me know if it is right?
I have a little confidence with this one but I don't know for sure.
To check the solution to
any "solving" problem, plug the solutions back into the original problem, and see if they work. If they do, then you'll
know ("for sure") that the solution is "right". :wink:
Helen said:
(x + 16) ^ (2) - 6 = 0
(x + 16 - 6)(x - 16 - 6) = 0
You might want to review the "difference of squares" formula. You appear to have tried to use "a[sup:3k1pe8za]2[/sup:3k1pe8za] - b[sup:3k1pe8za]2[/sup:3k1pe8za] = (a - b[sup:3k1pe8za]2[/sup:3k1pe8za])(a + b[sup:3k1pe8za]2[/sup:3k1pe8za])" but this is
not the correct formula! :shock:
Note: You might want to try using the completed-square method of solution:
i) Take a(x - h)[sup:3k1pe8za]2[/sup:3k1pe8za] + k = 0
ii) Isolate the squared binomial: a(x - h)[sup:3k1pe8za]2[/sup:3k1pe8za] = -k, so (x - h)[sup:3k1pe8za]2[/sup:3k1pe8za] = -k/a
iii) Take the square root of either side: x - h = +/- sqrt[ -k/a ]
iv) Isolate the variable: x = h +/- sqrt[ -k/a ]
In your case, a = 1, h = -16, and k = -6.
Eliz.